THE QUESTION OF GOD: PHENOMENOLOGY, HERMENEUTICS, AND REVELATION IN JEAN-LUC MARION AND PAUL RICOEUR - Dahl, Darren E. (My University, 2011)
This dissertation examines the thought of Jean-Luc Marion in light of his treatment of divine revelation and in connection to the hermeneutic phenomenology of Paul Ricoeur. It argues, first, that Marion’s thought bears within itself significant ambiguities that are determined by the legacies of the key concepts which organize his work: ‘givenness’ (donation) and saturation. Secondly, it also argues that even if a way can be found to resolve these ambiguities the resultant proposal does not meet the criticism raised by Paul Ricoeur in reference to phenomenologies of religion that remain determined by a ‘Husserlian idealism.’ As a result, the dissertation offers a study of Ricoeur’s hermeneutics of revelation in an effort to displace Marion’s account and offer an alternative proposal. Specifically, it treats the connection of Ricoeur’s proposed transformation of phenomenology through hermeneutics, the idea of a hermeneutics of testimony that is generated as a result of that transformation, and Ricoeur’s notion of revelation as being articulated in reference to the ‘world of the text.’ By focusing on the notion of ‘anteriority’ throughout the analysis, the dissertation argues that not only does Marion’s work remain limited by its formal commitments to pure apparition, but it fails to access the sort of radical anteriority that it seeks. This is so because it remains tied to a philosophy of consciousness which is blocked from accessing the pre-reflective level of belonging that is made accessible by Ricoeur’s hermeneutic phenomenology. By making this argument, the dissertation provides a critical analysis of Marion’s work from the perspective of divine revelation and, furthermore, brings that work into conversation with Paul Ricoeur. This important engagement between Ricoeur and Marion has not been adequately addressed in the current secondary literature and this dissertation fills that gap.
Keywords: revelation; phenomenology; hermeneutics; Jean-Luc Marion; Paul Ricoeur; Religious Thought, Theology and Philosophy of Religion; Religious Thought, Theology and Philosophy of Religion